2012
DOI: 10.1128/aem.06528-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Functional Gene Diversity with a Shift of Subsurface Redox Conditions during In Situ Uranium Reduction

Abstract: ABSTRACTTo better understand the microbial functional diversity changes with subsurface redox conditions duringin situuranium bioremediation, key functional genes were studied with GeoChip, a comprehensive functional gene microarray, in field experiments at a uranium mill tailings remedial action (UMTRA) site (Rifle, CO). The results indicated that functional microbial communities altered with a shift in the dominant metabolic process, as documented b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 35 publications
3
30
1
Order By: Relevance
“…The proportion of unexplained variation is comparable with that in a comprehensive biogeographic study (45). This result may be due to additional factors not measured in this study, such as the redox state of the sediment (46). However, some of the unexplained variation could also be due to ecologically neutral processes of diversification (i.e., evolutionary noise produced through random ecological drift) (39).…”
Section: Discussionsupporting
confidence: 64%
“…The proportion of unexplained variation is comparable with that in a comprehensive biogeographic study (45). This result may be due to additional factors not measured in this study, such as the redox state of the sediment (46). However, some of the unexplained variation could also be due to ecologically neutral processes of diversification (i.e., evolutionary noise produced through random ecological drift) (39).…”
Section: Discussionsupporting
confidence: 64%
“…This discrepancy may be explained because the primary amplification microarray signals for Desulfotomaculum came from Desulfotomaculum carboxydivorans, D. putei, and D. thermobenzoicum, species that are not necessarily detected by targeted aps primers that also amplify the aps gene from members of the Desulfobacteraceae (see Table 2 in reference 28) or with the highly degenerate aps primers described in reference 29. Prior field experiments and observations at the Rifle site also show consistent stimulation of sulfate-reducing lineages in response to acetate amendment (1,8) and an increase in dsr gene abundance, as measured by the comprehensive GeoChip microarray that uses whole-genome amplification methods instead of broad-range, gene-specific primers (2). We therefore attribute the discrepancy in sulfate reducer signals between qPCR and amplification microarray platforms in the Super 8 field experiment to limitations in the design and use of broad-spectrum functional gene primers for the qPCR and not 16S rRNA gene amplification microarray bias or the absence of Desulfotomaculum or other sulfate-reducing microbial potential within the gallery.…”
Section: Resultsmentioning
confidence: 99%
“…The effect could be particularly significant in U(VI)-contaminated groundwater like that at the Oak Ridge site, where electron donors and C sources are limited and multiple electron acceptors are present (6). Previous studies demonstrated that injection of fast-degrading, simple substrates (e.g., acetate or ethanol) stimulated distinct microbial communities (7,9,12,13). In this study, a slowly degrading, complex substrate, EVO, was used.…”
Section: Discussionmentioning
confidence: 99%
“…To remediate these sites, various fast-degrading substrates (e.g., acetate, ethanol, and lactate) have been used. The substrate injection stimulated microbial populations important to U(VI) reduction, resulting in distinct microbial communities whose functions were dependent upon the choice of substrate (6)(7)(8)(9)(10)(11)(12)(13). However, the use of these fast-degrading, simple substrates has several drawbacks.…”
mentioning
confidence: 99%